Maintenance of functional capacity in cognitive stimulation subgroups - Ferreira Santana, Rosimere; Batista Rosa, Thalita; Gonçalves Aquino, Raisa; Araújo de Alexandrino, Shardelle; Alves Santos, George Luiz; Araújo Lobato, Hanna (Investigación y Educación en Enfermería, 2016)
Objective. To evaluate the improvement of the elderly’s functional capacity before intervention in cognitive stimulation workshops, according to subgroups. Methods. Quantitative study, by before and after evaluation, following during one year the cognitive stimulation intervention, conducted according to recommendations of NIC (Nursing Interventions Classification) Domain 3 – Behavior, Class P, Cognitive Therapy “interventions to reinforce or promote desirable behaviors or to change undesirable behaviors”. Participants were 67 people, with ages between 60 and 88. The criteria for subgroups were: healthy= memory complaint and Mini Mental State Exam (MMSE) score above or equal to 26 (n = 20); low education level = memory complaint and up to 5 years of study (n = 11); depression = memory and humor complaint, and Geriatric Depression Scale (GDS) score ≥ 4 (n = 25); and the control group (n = 11), which did not receive the intervention, just the conventional treatment. Results. Although statistically significant differences have been observed in specific scores at each subgroup: MMSE (greater improvement in healthy elderly); GDS (greater improvement in the depression group); and the Word recall test (lower at the “low education level” group); it was noticed that at all intervention subgroups the functional capacity was maintained when compared to the control group. Conclusion. The cognitive stimulation workshops were useful to the elderly, who received the nursing intervention, the cognitive therapy. It is recommended adoption of the intervention in specific subgroups, according to their own cognitive limitations. How to cite this article: Santana RF, Rosa TB, Aquino RG, Alexandrino AS, Santos JLA. Maintenance functional capacity in cognitive stimulation subgroups. Invest. Educ. Enferm. 2016; 34(3): 492-501